2020
DOI: 10.3390/plants9121757
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of Soybean (Glycine max (L.) Merr.) Response to Blue Light Intensity in Controlled Environments

Abstract: Low photosynthetic photon flux density (PPFD) under shade is associated with low blue photon flux density (BPFD), which independent from PPFD can induce shade responses, e.g., elongation growth. In this study, the response of soybean to six levels of BPFD under constant PPFD from LED lighting was investigated with regard to morphology, biomass and photosynthesis to increase the knowledge for optimizing the intensity of BPFD for a speed breeding system. The results showed that low BPFD increased plant height, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…However, too much blue light reduced shoot fresh weight of tomato seedlings as blue light fraction increased from 50% to 75% in red plus blue LEDs [39] . In the study of Hitz et al [49] , who observed that dry weight and leaf area of soybean plants increased as fraction of blue light provided by red-blue LEDs increased from 15% to 27.5%, and a decreased trend was found as blue light fraction was more than 27.5%. In general, the increase in dry biomass accumulation in response to the supplementary light may be attributed to the augmented chlorophyll content and net photosynthetic rate.…”
Section: Discussionmentioning
confidence: 97%
“…However, too much blue light reduced shoot fresh weight of tomato seedlings as blue light fraction increased from 50% to 75% in red plus blue LEDs [39] . In the study of Hitz et al [49] , who observed that dry weight and leaf area of soybean plants increased as fraction of blue light provided by red-blue LEDs increased from 15% to 27.5%, and a decreased trend was found as blue light fraction was more than 27.5%. In general, the increase in dry biomass accumulation in response to the supplementary light may be attributed to the augmented chlorophyll content and net photosynthetic rate.…”
Section: Discussionmentioning
confidence: 97%
“…To record photosynthetic rates (A), the conditions in the measurement chamber of the device were set to 30 °C leaf temperature, 50% humidity and an ambient CO 2 concentration between 399 and 410 ppm. The red:far-red ratios were simulated in LED chambers, according to [ 49 ]. The KAN plants used for this purpose, grown under controlled greenhouse conditions, were in the fifth week of flowering (56 DAP), and the first fully developed main leaf (rank 4) was used.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the study of Hitz et al. [ 95 ] revealed that lower blue-light intensity could increase soybean leaf area and biomass, which is favorable for rapid soybean production; interestingly, the use of light-emitting diodes with the low blue light of 60 μmol·m −2 ·s −1 contributed to a reduced energy consumption by 7% compared to the control. Hence, a reasonable lighting scheme for SB strategies can be made available by achieving a satisfactory output (see Fig.…”
Section: Models Able To Assist For Sbmentioning
confidence: 99%